An isolated bidirectional inverter using high frequency center-tapped transformer - Salam, Zainal; Ramli, M. Z.; Toh, S. L.; Nge, L. C. (2004)
This paper proposes a bidirectional high-frequency link inverter using a high-frequency center-tapped transformer. The main feature of the inverter is fewer number of power switches used. On the secondary side of the transformer, the active rectifier employs only two switches, thus reducing the switching losses. Furthermore, a modified sinusoidal pulse width modulation (PWM) has been applied to increase the efficiency of the inverter. A 1 kW prototype has been constructed and experiments were carried out to verify the viability of the proposed inverter.